Associations and predictive value of isometric strength, isokinetic strength, and anaerobic power for 100-m freestyle performance in young swimmers - Zied Abbes; Rabeh Labbadi; Faten Salhi (Sport, Exercise, and Injury, 2026)
Background: Multiple physical and physiological factors influence sprint swimming performance; however, the relative contributions of isometric strength, isokinetic strength, and anaerobic power to 100-m freestyle performance in young swimmers remain unclear. Objectives: This study investigated the associations and predictive contributions of physical characteristics, isometric and isokinetic upper-body strength, and anaerobic power to 100-m freestyle swimming performance in young swimmers. Methods: A cross-sectional study was conducted with 21 male swimmers aged 10–13 years, selected purposively. Eligibility criteria included a minimum of three years of structured swimming training, regular participation in 3–5 training sessions per week, and absence of musculoskeletal injuries. Upper-body strength was assessed using isometric and isokinetic dynamometry (60°/s and 180°/s), while anaerobic power was measured using the 30-s Wingate Anaerobic Test. Swimming performance was evaluated using a 100-m freestyle time trial. Pearson correlation and linear regression analyses were performed after verification of regression assumptions. Results: Swimming speed was significantly correlated with isometric elbow flexor strength (r = .49, p < .05), isokinetic flexor strength at 60°/s (r = .41, p < .05), and Wingate peak power (r = .37, p < .05). Simple linear regression analysis identified isometric elbow flexor strength as the strongest predictor of swimming performance (B = 0.005, p = .026, R² = .235), followed by isokinetic flexor strength at 60°/s (B = 0.004, p = .038, R² = .210) and Wingate peak power (B = 0.001, p = .031, R² = .198). No significant associations were observed for isokinetic strength at 180°/s. Conclusions: Upper-body muscular strength, particularly isometric elbow flexor strength, is a significant determinant of 100-m freestyle swimming performance in young swimmers. These findings highlight the importance of maximal force-generating capacity, alongside anaerobic power development, for sprint swimming performance.